The Cooperative Learning Model of the STAD Type Assisted by Canva and Quizizz Media to Improve Students' Motivation, Activity, and Learning Outcomes - Ifan Fadilah; Koderi; Septuri (CV. Creative Tugu Pena, 2024)
This study aims to improve students' motivation, activities, and learning outcomes in Islamic Religious Education (PAI) by using the Student Teams Achievement Divisions (STAD) cooperative learning model, assisted by Canva and Quizizz media. The research method used is Classroom Action Research (CAR), conducted over three cycles. Each cycle consists of the stages of planning, action, observation, and reflection. The results indicate that implementing the STAD model, with Canva and Quizizz as supporting media, can enhance students' learning motivation, as reflected in increased activities during the learning process. Moreover, students' learning outcomes also showed significant improvement, as evidenced by the rise in average evaluation test scores in each cycle. In first cycle, the learning mastery rate was 63.16%, in second cycle it increased to 73.68%, and in third cycle it further increased to 89.47%. The use of Canva and Quizizz as tools in the STAD cooperative learning model proved effective in creating a fun and interactive learning environment, fostering students' enthusiasm and interest in learning.